Analisis pengaruh Harga, Lokasi dan Fasilitas terhadap Keputusan Memilih Rumah Kontrakan di Kelurahan Bandungrejosari Kecamatan Sukun Malang - Rikardus Jeharut; Iva Nurdiana Nurfarida; Candra Wahyu Hidayat (Jurnal Riset Mahasiswa Manajemen, 2018)
This study aims to determine whether the Price, Location, and Facilities affect the Decision to Choose. The independent variables in this study are Price, Location, Facilities, while the dependent variable in this study is the decision to choose. This research was conducted in Bandungrejosari Subdistrict, Sukun Malang District, using a sample of 112 respondents from home contractors. The sampling technique in this study used accidental sampling. The analysis technique used is multiple linear regression. The results of this study indicate that Price, Location, Facilities influence both partially and simultaneously the Voting Decision.